Method for producing hollow particles

The described method for producing hollow resin particles using suspension polymerization with a polar resin and inorganic metal salt dispersant addresses collapse and residual compound issues, resulting in stable, high-porosity particles with minimal volatile content.

JP7605130B2Active Publication Date: 2024-12-24ZEON CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2021562682
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-06-04
Filing Date
2020-12-02
Publication Date
2024-12-24
Estimated Expiration
2040-12-02

AI Technical Summary

Technical Problem

Existing methods for producing hollow resin particles result in products that are prone to collapse under shear and pressure during processing, have residual volatile compounds, and suffer from reduced strength due to fine through-holes and shell defects.

Method used

A method involving suspension polymerization using a polar resin, a poorly water-soluble inorganic metal salt as a dispersant, and a hydrocarbon solvent to create hollow particles with a high porosity and thick shell, minimizing residual volatile compounds and shell defects.

Benefits of technology

The method produces hollow particles that are resistant to crushing, maintain high porosity, and significantly reduce residual volatile compounds, ensuring stability during processing and improved mechanical strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007605130000004
    Figure 0007605130000004
  • Figure 0007605130000005
    Figure 0007605130000005
  • Figure 0007605130000006
    Figure 0007605130000006
Patent Text Reader

Abstract

Provided is a method for manufacturing hollow particles that have a high void ratio, can reduce the quantity of residue of solvents poorly soluble in water that are used in the manufacturing process, and are not prone to collapse. A method for manufacturing hollow particles, provided with a shell and a hollow section and having a void ratio of 50%–90%, characterized in that a liquid mixture including a polymerizable monomer for the shell, a polar resin, a hydrocarbon-based solvent, an inorganic metal salt poorly soluble in water as a dispersant, and a water-based medium is put in suspension to prepare a suspension in which droplets of a monomer composition that includes the polymerizable monomer for the shell, the polar resin, and the hydrocarbon-based solvent are dispersed in the water-based medium, the suspension is subjected to a polymerization reaction, and the hydrocarbon-based solvent is removed from the obtained hollow particles.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a method for producing hollow particles. More specifically, the present disclosure relates to a method for producing hollow particles that have a high porosity, are resistant to crushing, and can reduce the amount of residual volatile compounds, such as non-reactive hydrocarbon solvents and unreacted monomers, used in the production process, and are particularly resistant to crushing when kneaded with other materials, such as resins. [Background technology]

[0002] Hollow particles (hollow resin particles) produced by polymerizing monomers scatter light well and have low light transmittance compared to resin particles whose interiors are substantially filled with resin. Therefore, they are widely used as organic pigments or hiding agents with excellent optical properties such as opacity and whiteness in water-based paints, paper coating compositions, and the like.

[0003] It is desirable for hollow particles to have a high porosity in order to improve the effects of weight reduction, heat insulation, opacity, whitening, etc. of water-based paints, paper coating compositions, etc. However, when the porosity of hollow particles is increased, there is a problem that the shell thickness of the hollow particles becomes thin, making them more likely to be crushed. Therefore, hollow particles that have a high porosity and are not easily crushed are required.

[0004] Patent Document 1 discloses a method for producing hollow resin particles, which comprises dispersing a mixed solution containing a monomer mixture consisting of 20 to 70 parts by weight of a polyfunctional monomer having two or more ethylenically unsaturated groups and 80 to 30 parts by weight of a monofunctional monomer, a non-reactive organic solvent, and a non-crosslinkable polymer having a weight average molecular weight of 10,000 to 1,000,000 in terms of polystyrene, in an aqueous solution containing a dispersion stabilizer or a surfactant, and then polymerizing the resulting mixture. Patent Document 1 describes that the production method provides small-sized hollow resin particles with few pinholes and little crushing.

[0005] Patent Document 2 discloses hollow resin particles having one hollow surrounded by a shell, the hollow resin particles having a thermal decomposition starting temperature of 350° C. or higher, the shell having fine through-holes with diameters in the range of 10 to 50 nm, and a thickness ratio of 0.03 to 0.25 with respect to the average primary particle diameter of the hollow resin particles. Patent Document 2 also discloses that the hollow resin particles are produced by dispersing a mixed solution containing a polyfunctional monomer and a non-reactive solvent in an aqueous solution, and then polymerizing the polyfunctional monomer, that the aqueous solution may contain a dispersion stabilizer or a surfactant, and that it is preferable to use a water-soluble polymerization initiator to form fine through-holes with diameters of 10 to 50 nm.

[0006] Patent Document 3 discloses a method for producing hollow polymeric microparticles having a shell and a hollow portion with a single layer structure, which is characterized by dispersing a mixture of (i) at least one crosslinkable monomer (B) or a mixture of at least one crosslinkable monomer (B) and at least one monofunctional monomer (B') in an aqueous solution of a dispersion stabilizer (A), (ii) an initiator (C), and (iii) a water-insoluble solvent (D) having low compatibility with a polymer or copolymer obtained from at least one crosslinkable monomer (B) or a copolymer of at least one crosslinkable monomer (B) and at least one monofunctional monomer (B'), and performing suspension polymerization. Patent Document 3 also discloses that, as the dispersion stabilizer (A), a polymeric dispersion stabilizer such as polyvinyl alcohol, or a surfactant such as a nonionic surfactant, an anionic surfactant, or an amphoteric surfactant can be used, and among them, a polymeric dispersion stabilizer such as polyvinyl alcohol is preferable. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2016-68037 A [Patent Document 2] JP 2016-190980 A [Patent Document 3] JP 2002-80503 A Summary of the Invention [Problem to be solved by the invention]

[0008] However, the hollow resin particles obtained by the manufacturing method of Patent Document 1 have the problem that they are easily crushed when the hollow resin particles are mixed with a resin to prepare a paint or molding material, or when a molding material containing the hollow resin particles is used to produce a molded body, because they cannot sufficiently withstand the shear and pressure that occur during twin-screw kneading or injection molding.

[0009] The hollow resin particles obtained by the manufacturing method of Patent Document 2, like those of Patent Document 1, have a problem of being easily crushed because they cannot fully withstand the shear and pressure in twin-screw kneading and injection molding. In addition, the hollow resin particles obtained by the manufacturing method of Patent Document 2 have fine through-holes, so there is a problem that resin penetrates into the inside of the particles during injection molding of a molding resin composition containing the hollow resin particles. Furthermore, while the fine through-holes of the hollow resin particles may impart useful functions to the hollow resin particles, they also reduce the strength of the hollow resin particles and make them more susceptible to crushing because they are portions where the shell is missing.

[0010] The hollow resin particles obtained by the manufacturing method of Patent Document 3 have a problem in that the poorly water-soluble solvent present inside the hollow resin particles is difficult to remove after the hollow resin particles are formed by suspension polymerization, and therefore the poorly water-soluble solvent is likely to remain in the hollow resin particles. Furthermore, there is a risk that the residual solvent may cause fire or smoke when the hollow resin particles are mixed with a resin and kneaded with a twin-screw.

[0011] An object of the present disclosure is to provide a method for producing hollow particles that have a high porosity, are resistant to crushing, and can reduce the amount of residual volatile compounds, such as non-reactive hydrocarbon solvents and unreacted monomers, used in the production process. [Means for solving the problem]

[0012] The present inventors have noticed that in a method for obtaining hollow particles by suspension polymerization, in order to produce hollow particles that have a high porosity, are resistant to crushing, and can reduce the amount of residual volatile compounds, such as non-reactive hydrocarbon solvents and unreacted monomers, used in the production process, the type of resin contained in the mixed liquid used in the suspension polymerization and the type of dispersant used in the suspension polymerization are important.

[0013] According to the present disclosure, there is provided a method for producing hollow particles having a shell containing a resin and a hollow portion surrounded by the shell, and having a porosity of 50% or more and 90% or less, the method including a suspension step of preparing a suspension in which droplets of a monomer composition containing a polymerizable monomer for the shell, a polar resin selected from the group consisting of polymers containing a repeating unit containing a heteroatom, a hydrocarbon solvent, a poorly water-soluble inorganic metal salt as a dispersant, and an aqueous medium are dispersed in the aqueous medium by suspending the mixture containing a polymerizable monomer for the shell, a polar resin, and a hydrocarbon solvent, a polymerization step of subjecting the suspension to a polymerization reaction, and a hydrocarbon solvent removal step of removing the hydrocarbon solvent encapsulated in the hollow particles obtained by the polymerization step.

[0014] In the above production method, the mixed solution preferably contains 0.1 to 10 parts by mass of a polar resin with respect to 100 parts by mass of the shell polymerizable monomer.

[0015] In the above production method, the polar resin is preferably an acrylic polymer.

[0016] In the above-mentioned production method, it is preferable that the acrylic polymer, which is the polar resin, is a copolymer of polymerizable monomers for polar resins, including methyl methacrylate and a polar group-containing (meth)acrylic monovinyl monomer, and that the copolymerization ratio of the methyl methacrylate is 50.0 mass% or more and 99.9 mass% or less, and the copolymerization ratio of the polar group-containing (meth)acrylic monovinyl monomer is 0.1 mass% or more and 5.0 mass% or less, relative to 100 mass% of the total mass of the polymerizable monomers for polar resins.

[0017] In the above-mentioned production method, the poorly water-soluble inorganic metal salt serving as the dispersant is preferably magnesium hydroxide.

[0018] In the above-mentioned production method, the polymerizable monomer for the shell preferably contains a crosslinkable monomer in an amount of 70% by mass or more and 100% by mass or less and a non-crosslinkable monomer in an amount of 0% by mass or more and 30% by mass or less, based on a total mass of the polymerizable monomer for the shell being 100% by mass. Effect of the Invention

[0019] According to the manufacturing method of the present disclosure as described above, it is possible to produce hollow particles that have a high porosity, are resistant to crushing, and can reduce the amount of residual volatile compounds, such as non-reactive hydrocarbon solvents and unreacted monomers, used in the manufacturing process, and in particular, are resistant to crushing when kneaded with other materials such as resins. [Brief description of the drawings]

[0020] [Figure 1] 1A to 1C are diagrams illustrating an example of a manufacturing method according to the present disclosure. [Diagram 2] FIG. 2 is a schematic diagram showing an embodiment of a suspension in a suspending step. [Diagram 3] FIG. 1 is a schematic diagram showing a conventional dispersion for emulsion polymerization. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] 1. Manufacturing method of hollow particles The method for producing hollow particles in the present disclosure is a method for producing hollow particles having a shell containing a resin and a hollow portion surrounded by the shell, and having a porosity of 50% or more and 90% or less, and is characterized in that it includes a suspending step of preparing a suspension in which droplets of a monomer composition containing a polymerizable monomer for the shell, a polar resin selected from the group consisting of polymers containing a repeating unit containing a heteroatom, a hydrocarbon solvent, a poorly water-soluble inorganic metal salt as a dispersant, and an aqueous medium are dispersed in the aqueous medium by suspending a mixed liquid containing a polymerizable monomer for the shell, a polar resin, and a hydrocarbon solvent, a polymerization step of subjecting the suspension to a polymerization reaction, and a hydrocarbon solvent removal step of removing the hydrocarbon solvent encapsulated in the hollow particles obtained by the polymerization step.

[0022] The hollow particles of the present disclosure are particles having a shell (outer shell) containing a resin and a hollow portion surrounded by the shell. In the present disclosure, the hollow portion is a hollow space that is clearly distinguished from the shell of the hollow particle formed of a resin material. The shell of the hollow particle may have a porous structure, but in that case, the hollow portion has a size that is clearly distinguishable from the numerous minute spaces uniformly distributed within the porous structure. The hollow portion of the hollow particles can be confirmed, for example, by SEM observation of the cross section of the particle or by TEM observation of the particle itself. The hollow portion of the hollow particles may be filled with a gas such as air, or may contain a solvent. In addition, the hollow particles of the present disclosure usually have a shell that does not have a through hole or a shell defect, and the hollow part is isolated from the outside of the particle by the shell. In general, hollow particles include those in which the shell does not have a through hole that connects the hollow part to the outside space of the particle, and those in which the shell has one or more through holes and the hollow part is connected to the outside of the particle through the through hole. Although the through hole may impart a useful function to the hollow particle, it also causes the strength of the hollow particle to be reduced and makes it more likely to be crushed because it is a part where the shell is missing. The hollow particles of the present disclosure usually do not have through holes with a diameter of 10 nm or more and 500 nm or less. In addition, in the present disclosure, the shell defect of the hollow particle means a crack-like defect that is extremely large compared to the size of the particle, and causes the strength of the hollow particle to deteriorate. Although it depends on the size of the hollow particle, a crack having a length of 1 μm or more is generally recognized as a shell defect because it significantly deteriorates the strength of the hollow particle. In the present disclosure, the shell being free of interconnecting pores and shell defects means that the shell is substantially free of interconnecting pores and shell defects. When 100 hollow particles are observed using an SEM, if 5 or fewer hollow particles have interconnecting pores or shell defects, the shell is deemed to have no interconnecting pores or shell defects.

[0023] The method for producing hollow particles in the present disclosure follows the basic technique of suspending a mixed liquid containing a shell polymerizable monomer, a hydrocarbon solvent, a dispersant, and an aqueous medium, thereby preparing a suspension in which the shell polymerizable monomer and the hydrocarbon solvent are phase-separated, and droplets having a distribution structure in which the shell polymerizable monomer is unevenly distributed on the surface side and the hydrocarbon solvent is unevenly distributed in the center are dispersed in the aqueous medium, and the suspension is subjected to a polymerization reaction to harden the surfaces of the droplets and form hollow particles having hollow portions filled with the hydrocarbon solvent. In such a basic technique, by using a poorly water-soluble inorganic metal salt as a dispersant and adding a polar resin to the polymerizable monomer for the shell, it is possible to produce hollow particles that are resistant to crushing even with a high porosity and contain little residual volatile compounds such as hydrocarbon solvents and unreacted monomers.

[0024] The reason why the above-mentioned effects are obtained by the method for producing hollow particles according to the present disclosure is presumed to be as follows. The shell thickness of hollow particles is thought to have a significant effect on how difficult it is to crush. When comparing hollow particles with the same porosity but different particle sizes, the larger the particle size of the hollow particle, the thicker the shell will be, and the stronger the shell will be, making the hollow particle more difficult to crush. On the other hand, the shell thickness of hollow particles is thought to have a large effect on the efficiency of removing volatile compounds from hollow particles. After forming hollow particles by droplet polymerization, it is necessary to remove volatile compounds, such as the hydrocarbon solvent used as the spacer material to form the hollow portion and the unreacted polymerizable monomer for the shell, from the hollow particles. However, if the shell thickness of the hollow particles is too thick, it becomes difficult to remove the volatile compounds. Therefore, from the viewpoint of shell thickness, in order to obtain hollow particles that are resistant to crushing even with a high porosity and that contain little residual volatile compounds, it is important to adjust the particle size of the droplets containing the polymerizable monomer for the shell and the hydrocarbon solvent. The size of the droplets is influenced by the type of dispersant used in the suspension. For example, when a surfactant such as sodium dodecylbenzenesulfonate, as used in the inventions of Patent Documents 1 and 2, is used as a dispersant, droplets with small diameters are formed, and the diameters of hollow particles also become small, resulting in hollow particles with high porosity but that are easily crushed. Furthermore, for example, when polyvinyl alcohol as used in the invention of Patent Document 3 is used as a dispersant, large droplets are formed, and the diameter of hollow particles also becomes large, resulting in hollow particles with high porosity but from which it is difficult to remove volatile compounds.

[0025] Although poorly water-soluble inorganic metal salts can be used as dispersants, when poorly water-soluble inorganic metal salts are used without combining them with polar resins, large droplets are formed, resulting in hollow particles with large diameters, which have a high porosity but are difficult to remove volatile compounds from. In the present disclosure, the particle size of the droplets can be appropriately adjusted by using a poorly water-soluble inorganic metal salt in combination with a polar resin, so that hollow particles that are resistant to crushing even with a high porosity and have little residual volatile compounds can be obtained. When a mixed liquid containing a polymerizable monomer for the shell, a polar resin, a hydrocarbon-based solvent, a poorly water-soluble inorganic metal salt as a dispersant, and an aqueous medium is suspended, droplets consisting of a monomer composition containing the polymerizable monomer for the shell, the polar resin, and the hydrocarbon-based solvent are formed by the action of the dispersant, and a suspension is obtained in which the droplets are dispersed in the aqueous medium. The droplets have a structure in which the hydrocarbon solvent and the materials other than the hydrocarbon solvent, including the shell polymerizable monomer and the polar resin, are phase-separated, the hydrocarbon solvent is unevenly distributed in the center, the materials other than the hydrocarbon solvent are unevenly distributed on the surface side, the polar resin is unevenly distributed especially near the surface, and the poorly water-soluble inorganic metal salt is attached to the surface. Such a distribution structure of materials is formed according to the difference in affinity of each material for the aqueous medium. In the present disclosure, it is believed that the droplets in the suspension have a distribution structure of materials as described above, and an interaction occurs between the poorly water-soluble inorganic metal salt and the polar resin on the droplet surface, so that the dispersibility of the droplets due to the poorly water-soluble inorganic metal salt changes, and the particle size of the droplets containing the shell polymerizable monomer and the hydrocarbon solvent can be appropriately adjusted.

[0026] The hollow particles of the present disclosure are characterized by having extremely few interconnected pores in the shell and very few shell defects. Generally, hollow particles are classified into those in which the shell does not have a communicating hole that connects the hollow part with the external space of the particle, and those in which the shell has one or more communicating holes and the hollow part communicates with the outside of the particle via the communicating hole. Although it depends on the size of the hollow particle, the diameter of the communicating hole is usually about 10 to 500 nm. Although the communicating hole may impart a useful function to the hollow particle, it may also reduce the strength of the hollow particle and make it more likely to be crushed because it is a part where the shell is missing. In addition, hollow particles may have shell defects in the form of cracks that are extremely large compared to the size of the particle. Although it depends on the size of the hollow particle, cracks with a length of 1 μm or more are generally recognized as shell defects because they significantly reduce the strength of the hollow particle. In the present disclosure, it is believed that an interaction occurs between the poorly water-soluble inorganic metal salt and the polar resin on the droplet surface, which improves the condition of the hollow particle surface and allows the formation of a shell with extremely few interconnected pores and shell defects.

[0027] The above method basically includes a mixed solution preparation step, a suspension step, a polymerization step, and a hydrocarbon-based solvent removal step, but may include other steps. For example, after the polymerization step, solid-liquid separation may be performed, and a solvent removal step for removing the hydrocarbon-based solvent from the precursor particles may be performed under an air atmosphere. In addition, as far as technically possible, two or more of the above steps and other additional steps may be performed simultaneously as one step, or the order of the steps may be changed. For example, the preparation of the mixture and the suspension may be performed simultaneously in one process, such as by adding the materials for preparing the mixture and suspending them at the same time.

[0028] A preferred example of the manufacturing method according to the present disclosure includes the following steps. (1) Mixed liquid preparation process A step of preparing a mixed liquid containing a polymerizable monomer for the shell, a polar resin, a hydrocarbon-based solvent, a poorly water-soluble inorganic metal salt as a dispersant, and an aqueous medium. (2) Suspension process A step of preparing a suspension in which droplets of a monomer composition containing a polymerizable monomer for the shell, a polar resin, and a hydrocarbon-based solvent are dispersed in an aqueous medium by suspending the mixed liquid. (3) Polymerization process A step of subjecting the suspension to a polymerization reaction to prepare a precursor composition containing hollow particles (precursor particles) having hollow portions and containing a hydrocarbon-based solvent in the hollow portions. (4) Solid-liquid separation process A step of obtaining the hollow particles (precursor particles) by performing solid-liquid separation of the precursor composition; and (5) Solvent removal process A step of removing the hydrocarbon solvent contained in the hollow particles (precursor particles) obtained by the solid-liquid separation step. In the present disclosure, the hollow particles encapsulating the hydrocarbon solvent obtained by the polymerization step may be considered as intermediates of hollow particles whose hollow portions are filled with gas, and may be referred to as precursor particles. In the present disclosure, a composition containing the precursor particles is referred to as a precursor composition.

[0029] FIG. 1 is a schematic diagram showing an example of the manufacturing method of the present disclosure. (1) to (5) in FIG. 1 correspond to the above-mentioned steps (1) to (5). The white arrows between the figures indicate the order of the steps. Note that FIG. 1 is merely a schematic diagram for explanation, and the manufacturing method of the present disclosure is not limited to those shown in the figure. Furthermore, the structure, dimensions, and shape of the materials used in each manufacturing method of the present disclosure are not limited to the structure, dimensions, and shape of the various materials in these figures. 1(1) is a schematic cross-sectional view showing one embodiment of the mixed solution in the mixed solution preparation step. As shown in this figure, the mixed solution contains an aqueous medium 1 and a low-polarity material 2 dispersed in the aqueous medium 1. Here, the low-polarity material 2 refers to a material that has low polarity and is difficult to mix with the aqueous medium 1. In the present disclosure, the low-polarity material 2 includes a shell polymerizable monomer, a polar resin, and a hydrocarbon solvent. FIG. 1 (2) is a cross-sectional schematic diagram showing one embodiment of a suspension in a suspension preparation step. The suspension includes an aqueous medium 1 and droplets 10 dispersed in the aqueous medium 1. The droplets 10 include a shell polymerizable monomer, a polar resin, and a hydrocarbon solvent, but the distribution within the droplets is not uniform. The droplets 10 have a structure in which the hydrocarbon solvent 4a and the material other than the hydrocarbon solvent, including the shell polymerizable monomer and the polar resin, 4b, are phase-separated, the hydrocarbon solvent 4a is unevenly distributed in the center, the material other than the hydrocarbon solvent 4b is unevenly distributed on the surface side, the polar resin (not shown) is unevenly distributed especially near the surface, and a poorly water-soluble inorganic metal salt (not shown) is attached to the surface. 1(3) is a cross-sectional schematic diagram showing one embodiment of the precursor composition after the polymerization step. The precursor composition contains an aqueous medium 1 and precursor particles 20 dispersed in the aqueous medium 1. The shell 6 forming the outer surface of the precursor particle 20 is formed by polymerization of the monomers in the droplets 10. The hollow portion inside the shell 6 contains a hydrocarbon solvent 4a. Fig. 1(4) is a schematic cross-sectional view showing one embodiment of precursor particles after the solid-liquid separation step, in which the aqueous medium 1 has been separated from the state shown in Fig. 1(3). Fig. 1(5) is a cross-sectional schematic diagram showing one embodiment of hollow particles after a solvent removal step, in which the hydrocarbon solvent 4a has been removed from the state shown in Fig. 1(4). As a result, a hollow particle 100 having a hollow portion 8 inside the shell 6 is obtained. The above five steps and other steps will be described below in order.

[0030] (1) Mixed liquid preparation process This step is a step of preparing a mixed liquid containing a polymerizable monomer for the shell, a polar resin, a hydrocarbon-based solvent, a poorly water-soluble inorganic metal salt as a dispersant, and an aqueous medium. The polymerizable monomer is a compound having a polymerizable functional group. In the present disclosure, at least one polymerizable monomer selected from the group consisting of a non-crosslinkable monomer and a crosslinkable monomer is used as the polymerizable monomer. In the present disclosure, the polymerizable monomer for shell is a polymerizable monomer used to form the shell of a hollow particle. A non-crosslinkable monomer is a polymerizable monomer having only one polymerizable functional group, and a crosslinkable monomer is a polymerizable monomer having two or more polymerizable functional groups and forming a crosslinked bond in the resin by a polymerization reaction. As the polymerizable monomer, a compound having an ethylenically unsaturated bond as a polymerizable functional group is generally used. The mixture may further contain other materials such as an oil-soluble polymerization initiator, a suspension stabilizer, etc. The materials of the mixture will be described in the following order: (A) shell polymerizable monomer, (B) polar resin, (C) oil-soluble polymerization initiator, (D) hydrocarbon solvent, (E) dispersant, and (F) aqueous medium.

[0031] (A) Polymerizable monomer for shell [Non-crosslinkable monomer] As the non-crosslinkable monomer, a monovinyl monomer is preferably used. A monovinyl monomer is a compound having one polymerizable vinyl functional group. Examples of the monovinyl monomer include (meth)acrylic monovinyl monomers such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, glycidyl (meth)acrylate, and 2-hydroxyethyl (meth)acrylate; aromatic vinyl monomers such as styrene, vinyltoluene, α-methylstyrene, p-methylstyrene, and halogenated styrene; monoolefin monomers such as ethylene, propylene, and butylene; (meth)acrylamide monomers and derivatives thereof such as (meth)acrylamide, N-methylol (meth)acrylamide, and N-butoxymethyl (meth)acrylamide; diene monomers such as butadiene and isoprene; carboxylic acid vinyl ester monomers such as vinyl acetate; halogenated vinyl monomers such as vinyl chloride; halogenated vinylidene monomers such as vinylidene chloride; and vinylpyridine monomers. As the monovinyl monomer, among them, (meth)acrylic monovinyl monomers are preferred, and at least one selected from butyl acrylate and methyl methacrylate is more preferred, since the polymerization reaction is likely to be stable and hollow particles having high heat resistance can be obtained. In the present disclosure, (meth)acrylate means either acrylate or methacrylate, and (meth)acrylic means either acrylic or methacrylic. These non-crosslinkable monomers can be used alone or in combination of two or more kinds.

[0032] [Cross-linking monomer] In the present disclosure, the mechanical properties of the resulting hollow particle shell can be improved by using a crosslinkable monomer in combination with a non-crosslinkable monomer. In addition, since the crosslinkable monomer has multiple polymerizable functional groups, the monomers can be linked together, thereby increasing the crosslink density of the shell. Examples of the crosslinkable monomer include difunctional crosslinkable monomers such as divinylbenzene, divinyldiphenyl, divinylnaphthalene, diallyl phthalate, allyl (meth)acrylate, ethylene glycol di(meth)acrylate, and pentaerythritol di(meth)acrylate; and trifunctional or higher crosslinkable monomers such as trimethylolpropane tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, and dipentaerythritol hexa(meth)acrylate. Among these, divinylbenzene, ethylene glycol di(meth)acrylate, and pentaerythritol di(meth)acrylate are preferred, and ethylene glycol di(meth)acrylate and pentaerythritol di(meth)acrylate are more preferred. These crosslinkable monomers can be used alone or in combination of two or more kinds.

[0033] The content of the shell polymerizable monomers (all of the non-crosslinkable monomers and crosslinkable monomers) in the mixed solution is not particularly limited, but from the viewpoint of the balance between the porosity, particle size, and mechanical strength of the hollow particles, and from the viewpoint of reducing the amount of residual volatile compounds, the content is usually 15 to 55 mass%, more preferably 25 to 40 mass%, relative to 100 mass% of the total mass of the components in the mixed solution excluding the aqueous medium.

[0034] In the present disclosure, the content ratio of the crosslinkable monomer and the non-crosslinkable monomer in 100% by mass of the polymerizable monomer for the shell is 70% by mass or more and 100% by mass or less for the crosslinkable monomer, and 0% by mass or more and 30% by mass or less for the non-crosslinkable monomer. When the content ratio of the crosslinkable monomer is 70% by mass or more, the content ratio of the crosslinkable monomer unit in the shell of the hollow particle is sufficiently high, and a covalent bond network is densely spread throughout the shell, resulting in excellent strength, being difficult to crush, and being difficult to deform even when exposed to heat or the like applied from the outside. On the other hand, when the non-crosslinkable monomer is contained at a ratio of 30% by mass or less, the occurrence of shell interconnections and shell defects is further easily suppressed. In addition, when the polymerizable monomer for the shell contains the non-crosslinkable monomer, the content ratio of the crosslinkable monomer and the non-crosslinkable monomer in 100% by mass of the polymerizable monomer for the shell is not particularly limited, and may be, for example, 70% by mass or more and 95% by mass or less of the crosslinkable monomer and 5% by mass or more and 30% by mass or less of the non-crosslinkable monomer, or 70% by mass or more and 90% by mass or less of the crosslinkable monomer and 10% by mass or more and 30% by mass or less of the non-crosslinkable monomer.

[0035] (B) Polar resin (2) Polar resin The shell of the hollow particles of the present disclosure further comprises a polar resin. In the present disclosure, a polar resin refers to a polymer containing a repeating unit containing a heteroatom, and specific examples thereof include acrylic resins, polyester resins, and vinyl resins containing heteroatoms. The polar resin may be a homopolymer or copolymer of a heteroatom-containing monomer, or a copolymer of a heteroatom-containing monomer and a non-heteroatom-containing monomer. When the polar resin is a copolymer of a heteroatom-containing monomer and a non-heteroatom-containing monomer, the ratio of the heteroatom-containing monomer unit in 100% by mass of all repeating units constituting the copolymer is preferably 50% by mass or more, more preferably 70% by mass or more, and even more preferably 90% by mass or more, from the viewpoint of easy control of the particle diameter of the hollow particles. Examples of heteroatom-containing monomers used in polar resins include methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, acrylic acid, methacrylic acid, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, glycidyl (meth)acrylate, 4-hydroxybutyl a Examples of the monomers include (meth)acrylic monovinyl monomers having a (meth)acryloyl group, such as acrylate glycidyl ether; aromatic vinyl monomers containing heteroatoms, such as halogenated styrene and styrene sulfonic acid; vinyl carboxylate ester monomers, such as vinyl acetate; halogenated vinyl monomers, such as vinyl chloride; halogenated vinylidene monomers, such as vinylidene chloride; vinylpyridine monomers; carboxyl group-containing monomers, such as ethylenically unsaturated carboxylic acid monomers, such as crotonic acid, cinnamic acid, itaconic acid, fumaric acid, maleic acid, and butene tricarboxylic acid; and epoxy group-containing monomers, such as allyl glycidyl ether. These heteroatom-containing monomers may be used alone or in combination of two or more. Examples of heteroatom-free monomers used in polar resins include aromatic vinyl monomers not containing heteroatoms, such as styrene, vinyltoluene, α-methylstyrene, and p-methylstyrene; monoolefin monomers, such as ethylene, propylene, and butylene; and diene monomers, such as butadiene and isoprene. These heteroatom-free monomers can be used alone or in combination of two or more.

[0036] In particular, the polar resin is preferably an acrylic resin in which the total mass of (meth)acrylic monovinyl monomer units is preferably 50 mass% or more, more preferably 70 mass% or more, and even more preferably 90 mass% or more, of all repeating units constituting the resin (100 mass%), from the viewpoints of high compatibility with the polymerizable monomer for the shell and ease of controlling the particle diameter of the hollow particles. In particular, it is preferable that the polar resin is an acrylic resin in which all repeating units constituting the resin are composed of (meth)acrylic monovinyl monomer units.

[0037] In the polar resin, the heteroatom-containing monomer preferably contains a polar group-containing monomer unit containing a polar group selected from a carboxyl group, a hydroxyl group, a sulfonic acid group, an amino group, a polyoxyethylene group, and an epoxy group, in order to easily control the particle size of the hollow particles. As the polar group, a carboxyl group and a hydroxyl group are preferable in order to easily control the particle size of the hollow particles with a small amount of addition. Examples of polar group-containing monomers include carboxyl group-containing monomers such as ethylenically unsaturated carboxylic acid monomers such as acrylic acid, methacrylic acid, crotonic acid, cinnamic acid, itaconic acid, fumaric acid, maleic acid, and butene tricarboxylic acid; hydroxyl group-containing monomers such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate; sulfonic acid group-containing monomers such as styrenesulfonic acid; amino group-containing monomers such as dimethylaminoethyl (meth)acrylate and diethylaminoethyl (meth)acrylate; polyoxyethylene group-containing monomers such as methoxypolyethylene glycol (meth)acrylate; and epoxy group-containing monomers such as glycidyl (meth)acrylate, allyl glycidyl ether, and 4-hydroxybutyl acrylate glycidyl ether. These polar group-containing monomers can be used alone or in combination of two or more. When the polar resin contains a polar group-containing monomer unit, it is preferable that the polar group is located at the end of the main chain or side chain, or is bonded in a pendant manner to the main chain or side chain, since this makes it easier for the polar resin to be positioned on the outer surface of the hollow particle and makes it easier to control the particle size of the hollow particle.

[0038] When the polar resin does not contain the polar group-containing monomer unit, the heteroatom-containing monomer unit contained in the polar resin preferably contains a monomer unit derived from an alkyl(meth)acrylate, from the viewpoints of high compatibility with the polymerizable monomer for the shell and ease of control of the particle size of the hollow particles, and among these, from the viewpoint of high polarity, it is preferable to contain a monomer unit derived from an alkyl(meth)acrylate, preferably having an alkyl group with 3 or less carbon atoms, more preferably the alkyl group being a methyl group or ethyl group, and even more preferably the alkyl group being a methyl group.

[0039] The acrylic resin, which is the polar resin, is preferably a polymer or copolymer of a polymerizable monomer for a polar resin containing 50% by mass or more of methyl methacrylate when the total mass of the polymerizable monomer for a polar resin is taken as 100% by mass, because it has high compatibility with the polymerizable monomer for the shell and is easy to control the particle size of the hollow particles. In this disclosure, the polymerizable monomer used in the synthesis of the polar resin is referred to as the polymerizable monomer for a polar resin. The acrylic resin, which is the polar resin, is more preferably a copolymer of a polymerizable monomer for a polar resin containing 50.0% by mass or more and 99.9% by mass or less of methyl methacrylate and 0.1% by mass or more and 5.0% by mass or less of the polar group-containing monomer, from the viewpoint of easier control of the particle diameter of the hollow particles, still more preferably a copolymer of a polymerizable monomer for a polar resin containing 50.0% by mass or more and 99.0% by mass or less of methyl methacrylate and 0.1% by mass or more and 5.0% by mass or less of the polar group-containing monomer, and still more preferably a copolymer of a polymerizable monomer for a polar resin containing 50.0% by mass or more and 99.0% by mass or less of methyl methacrylate and 0.1% by mass or more and 5.0% by mass or less of the polar group-containing monomer, from the viewpoint of easier control of the particle diameter of the hollow particles. and 0.2% to 3.0% by mass of the polar group-containing monomer. The copolymer is particularly preferably a copolymer of polymerizable monomers for polar resins comprising 50.0% to 98.0% by mass of methyl methacrylate, 1.0% to 5.0% by mass of a (meth)acrylic monovinyl monomer different from methyl methacrylate and not containing the polar group, and 0.2% to 3.0% by mass of the polar group-containing monomer. The (meth)acrylic monovinyl monomer which is different from methyl methacrylate and does not contain a polar group is preferably at least one selected from ethyl acrylate and butyl acrylate, and particularly preferably ethyl acrylate, in terms of being able to control the glass transition temperature. As the polar group-containing monomer, from the viewpoint of compatibility with the polymerizable monomer for the shell, a (meth)acrylic monovinyl monomer containing a polar group is preferred, and from the viewpoint of the particle size control with a smaller addition amount, a (meth)acrylic monovinyl monomer containing a carboxyl group or a hydroxyl group is more preferred.

[0040] The polar resin can be obtained, for example, by polymerizing a polymerizable monomer for polar resins containing the heteroatom-containing monomer by a polymerization method such as solution polymerization or emulsion polymerization. Furthermore, when the polar resin is a copolymer, the copolymer may be any of a random copolymer, a block copolymer, or a graft copolymer, but is preferably a random copolymer. In addition, the polar resin is preferably pulverized as finely as possible in order to improve the solubility.

[0041] The number average molecular weight (Mn) of the polar resin is not particularly limited, but is preferably in the range of 3000 to 20000, more preferably in the range of 4000 to 17000, and even more preferably in the range of 6000 to 15000, in terms of polystyrene, measured by gel permeation chromatography (GPC) using tetrahydrofuran. When the number average molecular weight (Mn) of the polar resin is equal to or more than the lower limit, the solubility of the polar resin is improved and the particle size of the hollow particles can be easily controlled, and when it is equal to or less than the upper limit, a decrease in the strength of the shell can be suppressed.

[0042] In the hollow particles of the present disclosure, the content of the polar resin is preferably 0.1 parts by mass or more and 10 parts by mass or less, more preferably 0.3 parts by mass or more and 8.0 parts by mass or less, and even more preferably 0.5 parts by mass or more and 8.0 parts by mass or less, relative to 100 parts by mass of the shell polymerizable monomer. When the content of the polar resin is equal to or more than the lower limit, it is easy to control the particle diameter and shell thickness of the hollow particles, so that the strength of the hollow particles can be improved and the content of volatile compounds can be reduced. On the other hand, when the content of the polar resin is equal to or less than the upper limit, it is possible to suppress the decrease in the content ratio of the polymer derived from the shell polymerizable monomer, so that the decrease in the strength of the shell can be suppressed and the collapse of the hollow particles can be further suppressed.

[0043] (C) Oil-soluble polymerization initiator In the present disclosure, it is preferable to include an oil-soluble polymerization initiator in the mixed liquid. As a method for polymerizing droplets of the monomer composition after suspending the mixed liquid, there are an emulsion polymerization method using a water-soluble polymerization initiator and a suspension polymerization method using an oil-soluble polymerization initiator, and the suspension polymerization can be performed by using the oil-soluble polymerization initiator. The oil-soluble polymerization initiator is not particularly limited as long as it is lipophilic and has a solubility in water of 0.2% by mass or less. Examples of the oil-soluble polymerization initiator include benzoyl peroxide, lauroyl peroxide, t-butyl peroxide-2-ethylhexanoate, 2,2'-azobis(2,4-dimethylvaleronitrile), and azobisisobutyronitrile. When the total mass of the shell polymerizable monomers in the mixed solution is 100 parts by mass, the content of the oil-soluble polymerization initiator is preferably 0.1 to 10 parts by mass, more preferably 0.5 to 7 parts by mass, and even more preferably 1 to 5 parts by mass. By having the content of the oil-soluble polymerization initiator be 0.1 to 10 parts by mass, the polymerization reaction is allowed to proceed sufficiently, and there is little risk of the oil-soluble polymerization initiator remaining after completion of the polymerization reaction, and there is also little risk of an unexpected side reaction proceeding.

[0044] (D) Hydrocarbon solvents In the present disclosure, a hydrocarbon-based solvent is used as a non-polymerizable and poorly water-soluble organic solvent. The hydrocarbon-based solvent acts as a spacer material that forms a hollow portion inside the particle. In the suspension process described below, a suspension is obtained in which droplets of a monomer composition containing a hydrocarbon-based solvent are dispersed in an aqueous medium. In the suspension process, phase separation occurs in the droplets of the monomer composition, and as a result, the hydrocarbon-based solvent with low polarity tends to gather inside the polymerizable monomer droplets. Finally, in the droplets of the monomer composition, the hydrocarbon-based solvent is distributed inside the droplets, and other materials other than the hydrocarbon-based solvent are distributed around the droplets according to their respective polarities. Then, in the polymerization step described below, a precursor composition containing precursor particles encapsulating the hydrocarbon solvent is obtained. That is, the hydrocarbon solvent collects inside the particles, and hollow portions filled with the hydrocarbon solvent are formed inside the obtained precursor particles.

[0045] The type of the hydrocarbon solvent is not particularly limited. Examples of the hydrocarbon solvent include saturated hydrocarbon solvents such as butane, pentane, normal hexane, cyclohexane, heptane, and octane, aromatic hydrocarbon solvents such as benzene, toluene, and xylene, and relatively volatile solvents such as carbon disulfide and carbon tetrachloride. The porosity of the hollow particles can be adjusted by changing the amount of the hydrocarbon solvent in the mixture. In the suspension step described below, the polymerization reaction proceeds in a state in which the oil droplets containing the crosslinkable monomer and the like contain the hydrocarbon solvent, so that the porosity of the obtained hollow particles tends to increase as the content of the hydrocarbon solvent increases. The hydrocarbon solvent preferably contains a saturated hydrocarbon solvent in a total amount of 100% by mass. This allows sufficient phase separation to occur in the droplets of the polymerizable monomer, making it easy to obtain hollow particles having only one hollow portion, and suppresses the generation of porous particles. The ratio of the saturated hydrocarbon solvent is preferably 60% by mass or more, more preferably 80% by mass or more, in order to further suppress the generation of porous particles and to make the hollow portions of each hollow particle uniform. Moreover, the hydrocarbon solvent is preferably a hydrocarbon solvent having 4 to 7 carbon atoms. A hydrocarbon compound having 4 to 7 carbon atoms is easily encapsulated in the precursor particles during the polymerization step, and can be easily removed from the precursor particles during the solvent removal step. Among them, a hydrocarbon solvent having 5 or 6 carbon atoms is particularly preferred. Although not particularly limited, the hydrocarbon solvent preferably has a boiling point of 130° C. or less, more preferably 100° C. or less, in order to be easily removed in the solvent removal step described below. Moreover, the hydrocarbon solvent preferably has a boiling point of 50° C. or more, more preferably 60° C. or more, in order to be easily encapsulated in the precursor particles.

[0046] In addition, the hydrocarbon solvent preferably has a relative dielectric constant of 3 or less at 20°C. The relative dielectric constant is one of the indices that indicate the polarity of a compound. When the relative dielectric constant of the hydrocarbon solvent is sufficiently small, 3 or less, it is considered that phase separation proceeds quickly in the droplets of the polymerizable monomer, and hollow spaces are easily formed. Examples of solvents with a dielectric constant of 3 or less at 20°C are as follows. The value in parentheses is the dielectric constant value. Heptane (1.9), cyclohexane (2.0), benzene (2.3), toluene (2.4). For the relative dielectric constant at 20°C, values ​​described in known documents (for example, "Chemical Handbook Basic Edition" edited by the Chemical Society of Japan, revised 4th edition, Maruzen Co., Ltd., published on September 30, 1993, pages II-498 to II-503) and other technical information can be referenced. Examples of methods for measuring the relative dielectric constant at 20°C include a relative dielectric constant test performed in accordance with JISC 2101:1999, Section 23, at a measurement temperature of 20°C.

[0047] In the present disclosure, the content of the hydrocarbon solvent in the mixed solution is preferably 50 parts by mass or more and 500 parts by mass or less relative to 100 parts by mass of the total mass of the shell polymerizable monomer, because it is easy to control the particle size of the hollow particles, it is easy to increase the porosity while maintaining the strength of the hollow particles, and it is easy to reduce the amount of residual hydrocarbon solvent in the particles. The content of the hydrocarbon solvent in the mixed solution is preferably 60 parts by mass or more and 400 parts by mass or less, more preferably 70 parts by mass or more and 300 parts by mass or less, and even more preferably 80 parts by mass or more and 200 parts by mass or less relative to 100 parts by mass of the total mass of the shell polymerizable monomer.

[0048] (E) Dispersant The dispersant is an agent for dispersing droplets of the monomer composition in an aqueous medium in the suspension process. In the present disclosure, a poorly water-soluble inorganic metal salt is used as the dispersant. By using a poorly water-soluble inorganic metal salt, droplets having a large particle size can be formed in the suspension, so that the shell becomes thicker after polymerization, and the hollow particles are less likely to be crushed. Examples of poorly water-soluble inorganic metal salts include magnesium hydroxide, calcium hydroxide, barium hydroxide, calcium phosphate, etc. These poorly water-soluble inorganic metal salts may be used alone or in combination of two or more kinds. Among these poorly water-soluble inorganic metal salts, magnesium hydroxide can be preferably used, since it is easy to control the particle size of the droplets in the suspension and it is possible to narrow the particle size distribution of the obtained hollow particles. In the present disclosure, the poorly water-soluble inorganic metal salt is preferably an inorganic metal salt having a solubility of 0.5 g or less in 100 g of water.

[0049] When the total mass of the shell polymerizable monomer and the hydrocarbon solvent is 100 parts by mass, the content of the dispersant is preferably 0.5 to 10 parts by mass, more preferably 1.0 to 8.0 parts by mass. By making the content of the dispersant 0.5 parts by mass or more, the droplets of the monomer composition can be sufficiently dispersed so as not to be united in the suspension. On the other hand, by making the content of the dispersant 10 parts by mass or less, the viscosity of the suspension can be prevented from increasing during granulation, and the problem of the suspension being unable to pass through the granulator can be avoided. The content of the dispersant is usually from 2 to 15 parts by mass, and more preferably from 3 to 8 parts by mass, per 100 parts by mass of the aqueous medium, for the same reasons as above.

[0050] (F)Aqueous medium In the present disclosure, an aqueous medium means a medium selected from the group consisting of water, a hydrophilic solvent, and a mixture of water and a hydrophilic solvent. The hydrophilic solvent in the present disclosure is not particularly limited as long as it is sufficiently miscible with water and does not cause phase separation. Examples of the hydrophilic solvent include alcohols such as methanol and ethanol, tetrahydrofuran (THF), and dimethyl sulfoxide (DMSO). Among aqueous media, water is preferably used due to its high polarity. When using a mixture of water and a hydrophilic solvent, it is important that the polarity of the entire mixture is not too low from the viewpoint of forming droplets of the monomer composition. In this case, for example, the mixture ratio (mass ratio) of water to hydrophilic solvent may be water:hydrophilic solvent=99:1 to 50:50, etc.

[0051] The above-mentioned materials and other materials as necessary are mixed and appropriately stirred to obtain a mixed liquid. In the mixed liquid, the oil phase containing the above-mentioned (A) shell polymerizable monomer, (B) polar resin, (C) oil-soluble polymerization initiator, and (D) oleophilic material such as a hydrocarbon solvent is dispersed with particle sizes of about several mm in the aqueous phase containing (E) dispersant and (F) aqueous medium. The dispersion state of these materials in the mixed liquid can be observed with the naked eye depending on the type of material. In the mixed solution preparation step, the mixed solution may be obtained by simply mixing the above-mentioned materials and other materials as necessary and appropriately stirring, etc., but in order to make the shell more uniform, it is preferable to prepare a mixed solution by separately preparing an oil phase containing a polymerizable monomer for the shell, a polar resin, and a hydrocarbon-based solvent, and an aqueous phase containing a dispersant and an aqueous medium in advance and mixing them. By separately preparing the oil phase and the aqueous phase in advance in this way and then mixing them, hollow particles having a uniform composition in the shell portion can be produced.

[0052] (2) Suspension process The suspending step is a step of suspending the above-mentioned mixed liquid to prepare a suspension in which droplets of the monomer composition containing a hydrocarbon solvent are dispersed in an aqueous medium. The method of suspending the monomer composition to form droplets is not particularly limited, but may be carried out using, for example, an apparatus capable of strong stirring, such as an in-line emulsifying disperser (manufactured by Pacific Machinery Works, product name: Milder) or a high-speed emulsifying disperser (manufactured by Primix Corporation, product name: TK Homomixer MARK II type). In the suspension prepared in the suspending step, droplets of the monomer composition containing the lipophilic material and having a particle size of about 4.0 to 13.0 μm are uniformly dispersed in the aqueous medium. Such droplets of the monomer composition are difficult to observe with the naked eye, but can be observed using a known observation device such as an optical microscope. In the suspension step, phase separation occurs in the droplets of the monomer composition, and the hydrocarbon solvent having low polarity tends to collect inside the droplets. As a result, the resulting droplets have the hydrocarbon solvent distributed inside and materials other than the hydrocarbon solvent distributed around the periphery.

[0053] As described above, the present disclosure employs the suspension polymerization method rather than the emulsion polymerization method. Hereinafter, the advantages of the suspension polymerization method and the use of an oil-soluble polymerization initiator will be described in comparison with the emulsion polymerization method. Fig. 3 is a schematic diagram showing a dispersion liquid for emulsion polymerization, in which a micelle 60 is shown in a schematic cross section. 3 shows a state in which micelles 60, micelle precursors 60a, monomers 54c dissolved in the solvent, and a water-soluble polymerization initiator 55 are dispersed in an aqueous medium 51. The micelles 60 are formed by surrounding an oil-soluble monomer composition 54 with a surfactant 53. The monomer composition 54 contains monomers and the like that are raw materials for a polymer, but does not contain a polymerization initiator. On the other hand, the micelle precursor 60a is an aggregate of the surfactant 53, but does not contain a sufficient amount of the monomer composition 54. The micelle precursor 60a grows into a micelle 60 by incorporating the monomer 54c dissolved in the solvent and by procuring a part of the monomer composition 54 from other micelles 60, etc. The water-soluble polymerization initiator 55 penetrates into the micelles 60 and the micelle precursors 60a while diffusing in the aqueous medium 51, and promotes the growth of oil droplets inside them. Therefore, in the emulsion polymerization method, although each micelle 60 is monodispersed in the aqueous medium 51, the particle size of the micelles 60 is expected to grow to several hundreds of nm.

[0054] Fig. 2 is a schematic diagram showing one embodiment of the suspension in the suspending step. A droplet 10 of the monomer composition in Fig. 2 is intended to show a schematic cross section. Note that Fig. 2 is merely a schematic diagram, and the suspension in the present disclosure is not necessarily limited to that shown in Fig. 2. A part of Fig. 2 corresponds to (2) in Fig. 1 described above. 2 shows droplets 10 of a monomer composition and polymerizable monomers 4c (including non-crosslinkable monomers and crosslinkable monomers) dispersed in the aqueous medium 1. The droplets 10 are formed by surrounding an oil-soluble monomer composition 4 with a dispersant 3. The monomer composition contains an oil-soluble polymerization initiator 5, as well as polymerizable monomers (including non-crosslinkable monomers and crosslinkable monomers), a polar resin, and a hydrocarbon solvent (none of which are shown). The droplets 10 are minute oil droplets containing a monomer composition 4, and the oil-soluble polymerization initiator 5 generates polymerization initiation radicals inside the minute oil droplets. Therefore, precursor particles having a desired particle size can be produced without causing the minute oil droplets to grow too much. In addition, as can be seen by comparing suspension polymerization (FIG. 2) with emulsion polymerization (FIG. 3), in suspension polymerization (FIG. 2), there is no opportunity for the oil-soluble polymerization initiator 5 to come into contact with the polymerizable monomer 4c dispersed in the aqueous medium 1. Therefore, by using an oil-soluble polymerization initiator, it is possible to suppress the generation of excess polymer particles such as dense solid particles having a relatively small particle size in addition to the intended resin particles having hollow portions.

[0055] In the manufacturing method of the present disclosure, by using a poorly water-soluble inorganic metal salt as the dispersant 3, it is possible to form fine oil droplets with a larger particle size in the suspension compared to the case where other dispersants are used. Therefore, it is possible to obtain hollow particles with a thicker shell after polymerization that are less likely to be crushed. In addition, in the manufacturing method of the present disclosure, the particle size of the oil microdroplets can be easily controlled by containing a polar resin in the monomer composition 4. This makes it possible to prevent the shell thickness after polymerization from increasing excessively, and to reduce the amount of residual volatile compounds.

[0056] (3) Polymerization process This step is a step of preparing a precursor composition containing precursor particles having hollow portions and encapsulating a hydrocarbon solvent in the hollow portions by subjecting the above-mentioned suspension to a polymerization reaction. In the polymerization process, the shell polymerizable monomer in the droplets of the monomer composition is polymerized while the droplets still contain the hydrocarbon-based solvent, thereby forming precursor particles having a shell containing a resin, which is a polymer of the shell polymerizable monomer, and a hollow portion filled with the hydrocarbon-based solvent. In the manufacturing method of the present disclosure, the droplets of the monomer composition are subjected to a polymerization reaction while containing a hydrocarbon-based solvent, so that the polymerization reaction proceeds easily while maintaining the shape, and the size and porosity of the precursor particles are easily adjusted. In addition, since the shell polymerizable monomer and the hydrocarbon-based solvent are used in combination, the polarity of the hydrocarbon-based solvent is low with respect to the shell of the precursor particles, and the hydrocarbon-based solvent is not easily compatible with the shell, so that phase separation occurs sufficiently and the hollow portion is likely to be only one. In addition, the size and porosity of the precursor particles can be easily adjusted by adjusting the amount of the hydrocarbon-based solvent, the amount of the polar resin, the type of the dispersant, etc. The polymerization method is not particularly limited, and for example, a batch method, a semi-continuous method, a continuous method, etc. can be used. The polymerization temperature is preferably 40 to 80° C., more preferably 50 to 70° C. The polymerization reaction time is preferably 1 to 20 hours, more preferably 2 to 15 hours.

[0057] (4) Solid-liquid separation process This step is a step of obtaining a solid content containing precursor particles encapsulating a hydrocarbon-based solvent by solid-liquid separation of the above-mentioned precursor composition.

[0058] The method for performing solid-liquid separation of the precursor composition is not particularly limited, and a known method can be used. Examples of the solid-liquid separation method include centrifugation, filtration, and static separation. Among these, centrifugation or filtration can be used, and centrifugation may be used from the viewpoint of ease of operation. After the solid-liquid separation step, any step such as a pre-drying step may be carried out before carrying out the solvent removal step described below. Examples of the pre-drying step include a step of pre-drying the solid content obtained after the solid-liquid separation step using a drying device such as a dryer or a drying tool such as a hand dryer.

[0059] (5) Solvent removal process This step is a step for removing the hydrocarbon solvent contained in the hollow particles (precursor particles) obtained in the solid-liquid separation step. By removing the hydrocarbon solvent contained in the precursor particles in air, the hydrocarbon solvent inside the precursor particles is replaced with air, and hollow particles filled with gas are obtained.

[0060] In this process, "in the air" strictly means an environment in which no liquid exists outside the precursor particles, and an environment in which only a very small amount of liquid exists outside the precursor particles, which does not affect the removal of the hydrocarbon-based solvent. "In the air" can also be expressed as a state in which the precursor particles do not exist in a slurry, or a state in which the precursor particles exist in a dry powder. That is, in this process, it is important to remove the hydrocarbon-based solvent in an environment in which the precursor particles are in direct contact with the external gas.

[0061] The method for removing the hydrocarbon solvent from the precursor particles in the air is not particularly limited, and any known method can be used, such as reduced pressure drying, heat drying, air flow drying, or a combination of these methods. In particular, when the heat drying method is used, the heating temperature must be equal to or higher than the boiling point of the hydrocarbon solvent and equal to or lower than the maximum temperature at which the shell structure of the precursor particles does not collapse. Therefore, depending on the composition of the shell in the precursor particles and the type of the hydrocarbon solvent, the heating temperature may be, for example, 50 to 200°C, 70 to 180°C, or 100 to 150°C. By the drying operation in air, the hydrocarbon solvent inside the precursor particles is replaced by the external gas, resulting in hollow particles whose hollow portions are filled with gas.

[0062] The drying atmosphere is not particularly limited and can be appropriately selected depending on the application of the hollow particles. Examples of the drying atmosphere include air, oxygen, nitrogen, argon, etc. In addition, hollow particles with a temporary vacuum inside can be obtained by filling the inside of the hollow particles with a gas and then drying under reduced pressure.

[0063] As an alternative method, the hydrocarbon-based solvent may be removed by replacing the hydrocarbon-based solvent contained in the precursor particles in a slurry containing the precursor particles and an aqueous medium with the aqueous medium of the slurry, without subjecting the slurry-like precursor composition obtained in the polymerization step to solid-liquid separation. In this method, an inert gas is bubbled through the precursor composition at a temperature equal to or higher than the boiling point of the hydrocarbon solvent minus 35°C, thereby removing the hydrocarbon solvent contained in the precursor particles in the precursor composition, thereby reducing the amount of residual hydrocarbon solvent in the hollow particles. Here, when the hydrocarbon-based solvent is a mixed solvent containing multiple types of hydrocarbon-based solvents and has multiple boiling points, the boiling point of the hydrocarbon-based solvent in the solvent removal step is defined as the boiling point of the solvent with the highest boiling point among the solvents contained in the mixed solvent, i.e., the highest boiling point among the multiple boiling points. The temperature at which the inert gas is bubbled into the precursor composition is preferably a temperature equal to or higher than the boiling point of the hydrocarbon solvent minus 30°C, more preferably equal to or higher than the boiling point of the hydrocarbon solvent, in order to reduce the amount of the hydrocarbon solvent remaining in the hollow particles. The bubbling temperature is usually equal to or higher than the polymerization temperature in the polymerization step. Although not particularly limited, the bubbling temperature may be 50°C or higher and 100°C or lower. The inert gas to be bubbled is not particularly limited, but examples thereof include nitrogen and argon. The bubbling conditions are appropriately adjusted depending on the type and amount of the hydrocarbon solvent so as to remove the hydrocarbon solvent contained in the precursor particles, and are not particularly limited. For example, an inert gas may be bubbled at a rate of 1 to 3 L / min for 1 to 10 hours. In this method, an aqueous slurry is obtained in which the aqueous medium is encapsulated in the precursor particles. The slurry is subjected to solid-liquid separation to obtain hollow particles, which are then dried to remove the aqueous medium from the hollow particles, thereby obtaining hollow particles whose hollow spaces are filled with gas.

[0064] Comparing a method of obtaining hollow particles having hollow portions filled with gas by performing solid-liquid separation of a slurry-like precursor composition and then removing the hydrocarbon-based solvent in the precursor particles in air, with a method of obtaining hollow particles having hollow portions filled with gas by replacing the hydrocarbon-based solvent contained in precursor particles in a slurry containing precursor particles and an aqueous medium with the aqueous medium of the slurry, performing solid-liquid separation, and removing the aqueous medium in the precursor particles in air, the former method has the advantage that the hollow particles are less likely to be crushed in the step of removing the hydrocarbon-based solvent, and the latter method has the advantage that less residual hydrocarbon-based solvent is left by performing bubbling with an inert gas.

[0065] (6)Other As steps other than the above steps (1) to (5), for example, the following step (6-a) of cleaning and the following step (6-b) of replacing the hollow portion again may be added. (6-a) Cleaning process The washing step is a step of adding an acid or an alkali to wash the precursor composition containing the precursor particles before the solvent removal step in order to remove the dispersant remaining in the precursor composition containing the precursor particles. When the dispersant used is an inorganic compound soluble in acid, it is preferable to add an acid to the precursor composition containing the precursor particles to wash the precursor composition, whereas when the dispersant used is an inorganic compound soluble in alkali, it is preferable to add an alkali to the precursor composition containing the precursor particles to wash the precursor composition. Furthermore, when an inorganic compound soluble in acid is used as the dispersant, it is preferable to add an acid to the precursor composition containing the precursor particles to adjust the pH to preferably 6.5 or less, more preferably 6 or less. As the acid to be added, inorganic acids such as sulfuric acid, hydrochloric acid, nitric acid, etc., and organic acids such as formic acid, acetic acid, etc. can be used, but sulfuric acid is particularly preferable because it has a high efficiency of removing the dispersant and puts a small burden on the production equipment. (6-b) Re-replacement process of the hollow part The hollow re-substitution process is a process in which the gas or liquid inside the hollow particles is replaced with another gas or liquid. This substitution can change the environment inside the hollow particles, selectively confine molecules inside the hollow particles, or modify the chemical structure inside the hollow particles to suit the application.

[0066] 2.Hollow particles (1) Morphology of hollow particles The shape of the hollow particles is not particularly limited as long as a hollow space is formed inside, and examples thereof include a spherical shape, an oval spherical shape, an irregular shape, etc. Among these, a spherical shape is preferred from the viewpoint of ease of production. The hollow particles may have one or more hollow parts. The shell of the hollow particles and, when the hollow particles have two or more hollow parts, the partition walls separating the adjacent hollow parts may be porous. The inside of the particle preferably has only one hollow part in order to maintain a good balance between the high porosity of the hollow particles and the mechanical strength of the hollow particles. The hollow particles may have an average circularity of 0.950 to 0.995. An example of the shape of a hollow particle is a bag made of a thin membrane and inflated with gas, and its cross-sectional view is shown in hollow particle 100 in Fig. 1 (5) described later. In this example, a thin membrane is provided on the outside, and the inside is filled with gas. The particle shape can be confirmed by, for example, SEM or TEM. The internal shape of a particle can be confirmed by SEM or TEM after cutting the particle into slices by a known method. The hollow particles of the present disclosure may have a shell thickness of 0.020 μm or more and 1.20 μm or less, more preferably 0.100 μm or more and 1.00 μm or less, which makes it possible to suppress a decrease in mechanical strength while maintaining the porosity of the hollow particles. In the present disclosure, the shell thickness of a hollow particle is defined as the average thickness of 20 points on the shell of the hollow particle. The shell thickness of a hollow particle can be measured, for example, by breaking the hollow particle and observing the shell fragments with a SEM.

[0067] (2) Volume average particle diameter of hollow particles The lower limit of the volume average particle diameter of the hollow particles is preferably 4.0 μm or more, more preferably 4.5 μm or more, and even more preferably 5.0 μm or more, while the upper limit of the volume average particle diameter of the hollow particles is preferably 25.0 μm or less, more preferably 13.0 μm or less, even more preferably 12.0 μm or less, and particularly preferably 10.0 μm or less. When the volume average particle diameter of the hollow particles is equal to or greater than the lower limit, the hollow particles are less likely to aggregate with each other, and therefore exhibit excellent dispersibility. When the volume average particle diameter of the hollow particles is equal to or less than the upper limit, the hollow particles are less likely to be crushed, and therefore exhibit high mechanical strength.

[0068] (3) Hollow particle size distribution The particle size distribution of the hollow particles (volume average particle size (Dv) / number average particle size (Dn)) may be, for example, 1.1 or more and 2.5 or less. When the particle size distribution is 2.5 or less, particles with little variation in compressive strength characteristics and heat resistance between particles can be obtained. In addition, when a sheet-shaped molded product is produced, for example, a product with a uniform thickness can be produced by the particle size distribution being 2.5 or less. The volume average particle diameter (Dv) and number average particle diameter (Dn) of the hollow particles can be determined, for example, by measuring the particle diameter of the hollow particles using a laser diffraction particle size distribution analyzer, calculating the number average and volume average, and using the obtained values ​​as the number average particle diameter (Dn) and volume average particle diameter (Dv) of the particles. The particle size distribution is determined by dividing the volume average particle diameter by the number average particle diameter.

[0069] (4) Porosity of hollow particles The hollow particles obtained by the manufacturing method of the present disclosure have a porosity of 50% or more and 90% or less, preferably 50% or more and 85% or less, and more preferably 60% or more and 80% or less. By having a porosity of the above lower limit or more, the hollow particles are excellent in lightness, heat resistance, and heat insulation, and volatile compounds are less likely to remain inside the particles. In addition, by having a porosity of the above upper limit or less, the hollow particles are less likely to be crushed and have excellent strength.

[0070] The porosity of the hollow particles obtained by the manufacturing method of the present disclosure is the apparent density D 1 and true density D 0 It is calculated from: Apparent density of hollow particles D 1 The measurement method is as follows. First, a volume of 100 cm 3 30 cm into a measuring flask 3 The hollow particles are filled into the measuring flask, and the mass of the filled hollow particles is accurately weighed. Next, the measuring flask filled with the hollow particles is accurately filled with isopropanol up to the marked line, while being careful not to introduce air bubbles. The mass of isopropanol added to the measuring flask is accurately weighed, and the apparent density D of the hollow particles is calculated based on the following formula (I). 1 (g / cm 3 ) to calculate Formula (I) Apparent density D 1 = [Mass of hollow particles] / (100-[Mass of isopropanol]÷[Specific gravity of isopropanol at measurement temperature]) Apparent density D 1 corresponds to the specific gravity of the entire hollow particle when the hollow portion is considered to be a part of the hollow particle.

[0071] Hollow particle true density D 0 The measurement method is as follows: After crushing the hollow particles in advance, 3 The measuring flask is filled with about 10 g of crushed pieces of hollow particles, and the mass of the crushed pieces is accurately weighed. Then, in the same manner as in the measurement of the apparent density above, isopropanol is added to the measuring flask, the mass of isopropanol is accurately weighed, and the true density D of the hollow particles is calculated based on the following formula (II). 0 (g / cm 3 ) to calculate Formula (II) true density D 0 = [Mass of crushed hollow particle pieces] / (100-[Mass of isopropanol]÷[Specific gravity of isopropanol at the measurement temperature]) true density D 0corresponds to the specific gravity of only the shell part of the hollow particle. As is clear from the above measurement method, the true density D 0 In calculating the diameter of the hollow particles, the hollow portion is not considered to be part of the hollow particle.

[0072] The porosity (%) of a hollow particle is the apparent density D 1 and true density D 0 It is calculated by the following formula (III). Formula (III) Porosity (%) = 100 - (apparent density D 1 / true density D 0 ) x 100 The porosity of a hollow particle can be expressed as the proportion of the hollow portion in the specific gravity of the hollow particle.

[0073] (5) Shell thickness The hollow particles of the present disclosure have a shell thickness of 0.2 μm or more and less than 0.9 μm, preferably 0.2 μm or more and 0.8 μm or less, more preferably 0.25 μm or more and 0.7 μm or less, even more preferably 0.25 μm or more and 0.6 μm or less, and even more preferably 0.25 μm or more and 0.5 μm or less. The shell thickness of the hollow particles can be calculated by calculating the inner diameter r of the hollow particles according to the following formula (1) using the volume average particle diameter R and porosity of the hollow particles, and then calculating the inner diameter r and the volume average particle diameter R according to the following formula (2). 4 / 3π×(R / 2) 3 ×Porosity=4 / 3π×(r / 2) 3 Formula (1) Shell thickness = (Rr) / 2 Equation (2) The difference between the shell thickness calculated in this manner and the average thickness measured at 20 points on the shell is usually within ±10% of these average values, so the shell thickness calculated as described above can be regarded as the shell thickness of the hollow particles. The thickness at each point of the shell of a hollow particle used to calculate the average thickness at 20 points on the shell can be measured, for example, by breaking a hollow particle and observing a piece of the shell with an SEM.

[0074] (6) Content of volatile compounds The hollow particles obtained by the manufacturing method of the present disclosure preferably have a volatile compound content of 0.5% by mass or less, more preferably 0.3% by mass or less, and even more preferably 0.2% by mass or less, based on the total mass of the hollow particles (100% by mass). By having the volatile compound content in the hollow particles be equal to or less than the upper limit, there is no risk of the volatile compound in the hollow particles volatilizing to cause foaming or ignition when the hollow particles of the present disclosure are kneaded with other materials, and the specific gravity of the hollow particles can be reduced, thereby improving the effect as a lightweight material. In the present disclosure, the volatile compound refers to a compound that volatilizes when the resin composition containing the hollow particles of the present disclosure is kneaded, and typically refers to a compound that volatilizes when the resin composition containing the hollow particles of the present disclosure is melt-kneaded. The volatile compound is usually a compound having a boiling point of 235° C. or less and a molecular weight of 200 or less. The volatile compound contained in the hollow particles is typically a hydrocarbon solvent used in the production of the hollow particles and an unreacted polymerizable monomer remaining in the particles. The content of volatile compounds in hollow particles is measured by the following method. First, about 100 mg of hollow particles are placed in a 30 mL screw-top glass bottle and weighed accurately. Next, about 10 g of tetrahydrofuran (THF) is placed in the bottle and weighed accurately. The mixture in the glass bottle is stirred with a stirrer for 1 hour to extract the volatile compounds contained in the hollow particles. The stirring is stopped, the resin components of the hollow particles that are insoluble in THF are precipitated, and the precipitate is filtered to obtain a sample liquid. Filtration can be performed, for example, by attaching a filter (manufactured by Advantec, product name: Membrane Filter 25JP020AN) to a syringe. The sample liquid is analyzed by gas chromatography (GC), and the amount of volatile compounds (mass%) per unit mass contained in the hollow particles is determined from the GC peak area and a calibration curve created in advance. Detailed analysis conditions are as follows. (Analysis conditions) Equipment: GC-2010 (Shimadzu Corporation) Column: DB-5 (Agilent Technologies, Inc.) Film thickness 0.25μm, inner diameter 0.25mm, length 30m Detector: FID Carrier gas: Nitrogen (linear velocity: 28.8 cm / sec) Inlet temperature: 200℃ Detector temperature: 250℃ Oven temperature: Increase from 40°C to 230°C at a rate of 10°C / min, and hold at 230°C for 2 minutes. Sampling volume: 2μL

[0075] 3. Uses of hollow particles The hollow particles may be used, for example, as an undercoat material for thermal paper. In general, undercoat materials are required to have heat insulation and shock-absorbing properties (cushioning properties), and in addition, heat resistance is required for thermal paper applications. The hollow particles of the present disclosure have a high porosity, a hollow shape that is not easily crushed, a number-average particle size that is small enough to ensure flatness during coating, and high heat resistance, so that they can meet these requirements. In addition, the hollow particles are useful, for example, as plastic pigments that are excellent in gloss, hiding power, etc. The hollow particles of the present disclosure are difficult to be crushed during kneading with other materials, and when added to a molded article, they are excellent in effects as a weight reducing material, a heat insulating material, a sound insulating material, a vibration damping material, etc., and thus are suitable as an additive for a molded article. The hollow particles of the present disclosure are difficult to be crushed even during kneading with a resin and during molding after kneading, and thus are particularly preferably used as an additive for a resin molded article. The molded article containing the hollow particles of the present disclosure may contain, as the resin, for example, a thermoplastic resin or a thermosetting resin such as polyethylene, polypropylene, polyvinyl chloride, polystyrene, polyurethane, epoxy resin, acrylonitrile-butadiene-styrene (ABS) resin, acrylonitrile-styrene (AS) resin, poly(meth)acrylate, polycarbonate, polyamide, polyimide, polyphenylene ether, polyphenylene sulfide, polyester, polytetrafluoroethylene, polyphenylene oxide, cyanate resin. Further, the molded article containing the hollow particles of the present disclosure may further contain fibers such as carbon fiber, glass fiber, aramid fiber, polyethylene fiber. The hollow particles obtained by the production method of the present disclosure can also be contained as a filler in a molded article formed using a thermoplastic or thermosetting resin, and a molded article formed using a material containing a thermoplastic or thermosetting resin and further containing fibers. Useful components such as fragrances, chemicals, agricultural chemicals, ink components, etc. can be encapsulated in the hollow particles by means such as impregnation treatment, reduced pressure or pressurized impregnation treatment. The hollow particles encapsulating such useful components can be used for various applications according to the components contained therein. The hollow particles can also be used for other members such as light reflecting materials, heat insulating materials, sound insulating materials and low dielectrics used in various fields such as automobiles, electrics, electronics, architecture, aviation, space, etc., and tableware containers.

Examples

[0076] Hereinafter, the present invention will be described more specifically with reference to Examples and Comparative Examples, but the present invention is not limited only to these Examples. In addition, parts and % are based on mass unless otherwise specified.

[0077] <A. Preparation of Polar Resin> [Production Example 1: Production of Polar Resin A (MMA / AA / EA Copolymer)] 200 parts of toluene were added to the reaction vessel, and the inside of the reaction vessel was thoroughly replaced with nitrogen while stirring the toluene, and then the temperature was raised to 90°C, and then a mixed solution of 96.2 parts of methyl methacrylate (MMA), 0.3 parts of acrylic acid (AA), 3.5 parts of ethyl acrylate (EA), and 2.8 parts of t-butylperoxy-2-ethylhexanoate (manufactured by NOF Corporation, trade name: Perbutyl O) was dropped into the reaction vessel over 2 hours. The mixture was further kept under toluene reflux for 10 hours to complete polymerization, and then the solvent was distilled off under reduced pressure to obtain polar resin A (MMA / AA / EA copolymer). Of the total mass of repeating units constituting the obtained polar resin A (MMA / AA / EA copolymer), 100%, the proportion of repeating units derived from MMA was 96.2%, the proportion of repeating units derived from AA was 0.3%, and the proportion of repeating units derived from EA was 3.5%. The number average molecular weight of the resulting polar resin A (MMA / AA / EA copolymer) was 10,000. The number average molecular weight was measured by gel permeation chromatography (GPC) using tetrahydrofuran as a carrier at a flow rate of 0.35 ml / min, and was calculated as a polystyrene equivalent molecular weight. The apparatus used was a Tosoh HLC8220, the column consisted of three Showa Denko Shodex (registered trademark) KF-404HQ columns connected together (column temperature 40°C), and the detectors used were a differential refractometer and an ultraviolet detector. Molecular weight calibration was performed using 12 standard polystyrene points (5 to 3 million) manufactured by Polymer Laboratory.

[0078] [Production Example 2: Production of Polar Resin B (MMA / HEMA / EA Copolymer)] 200 parts of toluene were added to the reaction vessel, and the inside of the reaction vessel was thoroughly replaced with nitrogen while stirring the toluene, and then the temperature was raised to 90°C, and then a mixed solution of 95.0 parts of methyl methacrylate (MMA), 3.0 parts of 2-hydroxyethyl methacrylate (HEMA), 2.0 parts of ethyl acrylate (EA), and 2.8 parts of t-butylperoxy-2-ethylhexanoate (manufactured by NOF Corporation, trade name: Perbutyl O) was dropped into the reaction vessel over 2 hours. The mixture was further kept under toluene reflux for 10 hours to complete polymerization, and then the solvent was distilled off under reduced pressure to obtain polar resin B (MMA / HEMA / EA copolymer). Of the total mass of repeating units constituting the obtained polar resin B (MMA / HEMA / EA copolymer), 100%, the proportion of repeating units derived from MMA was 95.0%, the proportion of repeating units derived from HEMA was 3.0%, and the proportion of repeating units derived from EA was 2.0%. The number average molecular weight of the resulting polar resin B (MMA / HEMA / EA copolymer) was 10,000.

[0079] [Production of polar resin C (PMMA)] 200 parts of toluene were added to the reaction vessel, and the inside of the reaction vessel was thoroughly replaced with nitrogen while stirring the toluene, and then the temperature was raised to 90°C, and then a mixed solution of 100 parts of methyl methacrylate (MMA) and 2.8 parts of t-butylperoxy-2-ethylhexanoate (manufactured by NOF Corporation, trade name: Perbutyl O) was dropped into the reaction vessel over 2 hours. The mixture was further kept under toluene reflux for 10 hours to complete polymerization, and then the solvent was distilled off under reduced pressure to obtain polar resin C (MMA homopolymer). The number average molecular weight of the obtained polar resin C (MMA homopolymer) was 6,000.

[0080] [Table 1]

[0081] In the above table, the meanings of each abbreviation are as follows: MMA: Methyl methacrylate AA: Acrylic acid EA: Ethyl acrylate HEMA: 2-Hydroxyethyl methacrylate

[0082] <B. Production of hollow particles> [Example 1] (1) Mixed solution preparation step First, the following materials were mixed to form an oil phase. 100 parts of ethylene glycol dimethacrylate 2 parts of polar resin A (MMA / AA / EA copolymer) 3 parts of 2,2’-azobis(2,4-dimethylvaleronitrile) (oil-soluble polymerization initiator, manufactured by Wako Pure Chemical Industries, Ltd., trade name: V-65) 187 parts of cyclohexane Next, in a stirring tank, at room temperature, an aqueous solution obtained by dissolving 7.8 parts of magnesium chloride (water-soluble polyvalent metal salt) in 225 parts of ion-exchanged water was gradually added with stirring to an aqueous solution obtained by dissolving 5.5 parts of sodium hydroxide (alkali metal hydroxide) in 55 parts of ion-exchanged water to prepare a magnesium hydroxide colloid (water-insoluble metal hydroxide colloid) dispersion, which was used as the aqueous phase. The obtained aqueous phase and oil phase were mixed to prepare a mixed solution.

[0083] (2) Suspension step The mixed solution obtained in the above mixed solution preparation step was stirred for 1 minute under the condition of a rotation speed of 4,000 rpm by a disperser (manufactured by Primix Corporation, trade name: Homomixer) to be suspended, and a suspension in which droplets of the monomer composition containing cyclohexane were dispersed in water was prepared.

[0084] (3) Polymerization step The suspension obtained in the above suspension step was stirred for 4 hours under the temperature condition of 65 °C in a nitrogen atmosphere to carry out a polymerization reaction. By this polymerization reaction, a precursor composition containing precursor particles encapsulating cyclohexane was prepared.

[0085] (4) Washing step and solid-liquid separation step The precursor composition obtained in the above polymerization step was washed with dilute sulfuric acid (at 25 °C for 10 minutes) to adjust the pH to 5.5 or less. Subsequently, after separating water by filtration, 200 parts of fresh ion-exchanged water was added to re-slurry, and the water washing treatment (washing, filtration, dehydration) was repeated several times at room temperature (25 °C), followed by filtration separation to obtain a solid content. The obtained solid content was dried in a dryer at a temperature of 40 °C to obtain precursor particles encapsulating cyclohexane.

[0086] (5) Solvent removal step The precursor particles obtained in the above solid-liquid separation step were heat-treated in a vacuum dryer at 200 °C for 6 hours under vacuum conditions to remove the hydrocarbon-based solvent in the hollow part, thereby obtaining the hollow particles of Example 1. From the observation results of a scanning electron microscope and the porosity values, it was confirmed that these particles were spherical and had a hollow part.

[0087] [Examples 2-9, Comparative Examples 1-8] In Example 1, except that the materials and amounts of the oil phase prepared in the above “(1) Mixed solution preparation step” were as shown in Table 1, and the amount of ion-exchanged water in the aqueous phase and the type and amount of the dispersant were as shown in Table 1, hollow particles of Examples 2-9 and Comparative Examples 1-8 were produced by the same procedure as in Example 1. Note that sodium dodecylbenzenesulfonate (surfactant) and polyvinyl alcohol were used as the dispersants in the comparative examples.

[0088] (C. Testing of hollow particles) The following measurements and evaluations were performed on the hollow particles obtained in Examples 1-9 and Comparative Examples 1-8.

[0089] (1) Volume average particle diameter of hollow particles Using a laser diffraction particle size distribution analyzer (manufactured by Shimadzu Corporation, product name: SALD-2000), the particle diameters of individual hollow particles were measured, and the volume average particle diameter was calculated assuming the hollow particles were spherical.

[0090] (2) Density and porosity of hollow particles (i) Measurement of the apparent density of hollow particles The measurement of the apparent density of the hollow particles was carried out in the same manner as the procedure described in the item of "(4) Porosity of hollow particles" in "2. Hollow particles".

[0091] (ii) Measurement of the true density of hollow particles The measurement of the true density of the hollow particles was carried out in the same manner as the procedure described in the item of "(4) Porosity of hollow particles" in "2. Hollow particles".

[0092] (iii) Calculation of porosity The calculation of the porosity of the hollow particles was carried out in the same manner as the procedure described in the item of "(4) Porosity of hollow particles" in "2. Hollow particles".

[0093] (3) Amount of volatile compounds in hollow particles Regarding the content of volatile compounds in the hollow resin particles, the procedure described in the item of "(6) Content of volatile compounds" in "2. Hollow particles" was carried out, and the amount of volatile compounds such as hydrocarbon solvents (cyclohexane (boiling point 80.74 °C, molecular weight 84.16), ethylene glycol dimethacrylate (boiling point 235 °C, molecular weight 198.22), methyl methacrylate (boiling point 101 °C, molecular weight 100.12), etc.) contained in the hollow particles was measured.

[0094] (4) SEM observation of hollow particles 100 hollow particles obtained in Examples 1 to 9 and Comparative Examples 1 to 8 were each observed by SEM, and in each particle, the presence or absence of through-holes with a size of 10 nm or more and 500 nm or less in diameter and cracks with a length of 1 μm or more was confirmed.

[0095] [Evaluation results of hollow particles] Table 2 shows the types and addition amounts of the materials used in Examples 1 to 9 and Comparative Examples 1 to 8, as well as the evaluation results regarding the hollow particles.

[0096]

Table 2

[0097] <D. Manufacture of molded body> [Example 10] As the thermoplastic resin, 90 parts of polypropylene (manufactured by Mitsubishi Chemical Corporation, trade name: MA1B, specific gravity 0.90 g / cm 3 ) and 10 parts of the hollow particles obtained in Example 1 were mixed with a blender. Next, the obtained resin composition was kneaded under the following kneading conditions using a twin-screw kneader (product name "TEM-35B", manufactured by Toshiba Machine Co., Ltd.), extruded, and pelletized to obtain pellets of the resin composition. Kneading conditions: Screw diameter 37 mm, L / D = 32 Screw rotation speed 250 rpm Resin temperature 190 °C Feed rate 20 kg / hour The obtained pellets of the resin composition were heated and dried at 80 °C for 6 hours, and then using an injection molding apparatus, a molded body with dimensions of 80 mm × 10 mm × thickness 4 mm was obtained under the following molding conditions. Molding conditions: Cylinder temperature: 230 °C Mold temperature: 40 °C Injection pressure: 70 MPa

[0098] [Examples 11 to 20, Comparative Examples 9 to 13] In Example 10, except that the type and amount of the thermoplastic resin were as shown in Table 2 and the type and amount of the hollow particles were as shown in Table 2, molded bodies of the resin compositions of Examples 11 to 20 and Comparative Examples 9 to 13 were produced in the same procedure as in Example 10. In Table 2, "PA-6" in the column of the thermoplastic resin is a commercially available polyamide resin (manufactured by Unitika Ltd., product name: A1020BRL, specific gravity 1.13 g / cm 3 ) and "glass balloon" in the column of the hollow particles is a commercially available glass hollow particle (manufactured by 3M Company, product name "Glass Bubbles iM30K", specific gravity 0.6 g / cm 3 )

[0099] <E. Testing of Molded Bodies> For each of the obtained molded bodies, the specific gravity of the molded body was measured, the weight reduction rate and specific gravity increase rate were calculated, and the variation in specific gravity was measured.

[0100] (1) Specific Gravity of Molded Body The specific gravity of the resulting molded product was measured by the underwater displacement method in accordance with JIS K 7112.

[0101] (2) Specific gravity of hollow particles The specific gravity of the hollow particles was determined using the apparent density values ​​shown in Table 2.

[0102] (3) Weight reduction rate The weight reduction rate was calculated using the following formula (4). [Formula (4)] Weight reduction rate (%) = 100 x (1 - specific gravity of molded body / specific gravity of thermoplastic resin alone)

[0103] (4) Gravity increase rate When the hollow particles in the thermoplastic resin composition, which is the molding material, are not crushed at all during injection molding, the specific gravity of the obtained molded body is the same as that of the thermoplastic resin composition. When the hollow particles in the molding material are crushed during injection molding, the specific gravity of the obtained molded body is larger than that of the thermoplastic resin composition, which is the molding material. Therefore, in order to evaluate the degree to which the hollow particles are crushed during injection molding, the ratio of the increase in the specific gravity of the obtained molded body to the theoretical specific gravity of the thermoplastic resin composition was calculated. The specific gravity increase rate was calculated by the following formula (5): The theoretical specific gravity of the thermoplastic resin was calculated from the weight ratio of the thermoplastic resin to the hollow particles and their respective specific gravities, and is shown in Table 3. [Formula (5)] Specific gravity increase rate (%) = 100 × (specific gravity of molded body / theoretical specific gravity of resin composition - 1)

[0104] [Evaluation results of molded products] Table 3 shows the types and amounts of the thermoplastic resins and hollow particles used in Examples 10 to 20 and Comparative Examples 9 to 13, as well as the evaluation results for the molded articles of the resin compositions.

[0105] [Table 3]

[0106] [Consideration] The evaluation results of each of the experimental examples and comparative examples will be discussed below with reference to Tables 2 and 3. In Comparative Example 1, the content of the hydrocarbon solvent in the mixed liquid was insufficient, so the porosity of the obtained hollow particles was small and the amount of volatile compounds was large. The reason for the large amount of volatile compounds is believed to be that the shell thickness of the hollow particles was thick due to the small porosity, making it difficult to remove the volatile compounds.

[0107] In Comparative Example 2, magnesium hydroxide, which is a poorly water-soluble inorganic metal salt, was added to the mixed solution, but no polar resin was added, so the volume average particle size of the obtained hollow particles was excessively large, and the amount of volatile compounds was large. The reason for the large amount of volatile compounds is believed to be that the volume average particle size of the hollow particles was large, which resulted in a thicker shell of the hollow particles, making it difficult to remove the hydrocarbon solvent from the hollow particles.

[0108] In Comparative Example 3, the content of the hydrocarbon solvent in the mixed liquid was too high, so that the obtained hollow particles had an excessively large porosity, as shown in Table 1. Therefore, the molded body of Comparative Example 9, which was produced using the hollow particles of Comparative Example 3, had a low weight reduction rate and an increased specific gravity increase rate. This is thought to be because the shell thickness of the hollow particles was thin due to the high porosity of the hollow particles, and the hollow particles were crushed during kneading with the thermoplastic resin or molding.

[0109] In Comparative Example 4, no polar resin was added, and instead, sodium dodecylbenzenesulfonate, a surfactant, was added as a dispersant, resulting in a small volume average particle size. As a result, the molded product of Comparative Example 10, which was produced using the hollow particles of Comparative Example 4, had a low weight reduction rate and an increased specific gravity increase rate. This is believed to be because the hollow particles had a small volume average particle size, so that a sufficient shell thickness could not be obtained, and the hollow particles were crushed during kneading with the thermoplastic resin or molding.

[0110] In Comparative Example 5, instead of the polar resin of Example 1, a component corresponding to the monomer of the polar resin was added in an amount equivalent to the copolymerization amount of the polar resin, and further, sodium dodecylbenzenesulfonate, a surfactant, was added in combination with magnesium hydroxide of Example 1 as a dispersant. As a result, the volume average particle size of the obtained hollow particles became excessively large, and the amount of volatile compounds became large. The reason for the increase in the amount of volatile compounds is considered to be that the shell thickness of the hollow particles became thicker due to the increase in the volume average particle size of the hollow particles, making it difficult to remove the hydrocarbon-based solvent from the hollow particles.

[0111] Comparative Example 6 was carried out in the same manner as Comparative Example 4, except that ethylene glycol dimethacrylate used as the crosslinkable monomer in Comparative Example 4 was replaced with dipentaerythritol hexaacrylate. As a result, in Comparative Example 6, no polar resin was added, and sodium dodecylbenzenesulfonate, a surfactant, was added as a dispersant, resulting in a small volume average particle size. For this reason, the molded body of Comparative Example 12, which was produced using the hollow particles of Comparative Example 6, had a low weight reduction rate and an increased specific gravity increase rate. This is believed to be because the hollow particles had a small volume average particle size, so that a sufficient shell thickness could not be obtained, and the hollow particles were crushed during kneading with the thermoplastic resin or during molding. In addition, 100 hollow particles obtained in Comparative Example 6 were observed by SEM, and as a result, 20 out of the 100 hollow particles were found to have continuous holes with diameters of 10 nm or more and 500 nm or less, or crack-like defects with lengths of 1 μm or more. This is presumably because in Comparative Example 6, no water-soluble inorganic metal salt was added, and only the surfactant sodium dodecylbenzenesulfonate was added, resulting in a small particle size, and because only a multifunctional acrylate with three or more functionalities was used as the polymerizable monomer for the shell, distortion occurred in the shell after polymerization.

[0112] In Comparative Example 7, 0.5 parts of poly(methyl methacrylate) was added as a polar resin, but polyvinyl alcohol was added as a dispersant, so the volume average particle size of the obtained hollow particles was excessively large, and the amount of volatile compounds was large. The reason for the increase in the amount of volatile compounds is believed to be that the volume average particle size of the hollow particles was increased, which resulted in a thicker shell of the hollow particles, making it difficult to remove the hydrocarbon solvent from the hollow particles.

[0113] In Comparative Example 8, a polar resin was added and sodium dodecylbenzenesulfonate, a surfactant, was added as a dispersant, but the volume average particle size was small. Therefore, the molded body of Comparative Example 13, which was made using the hollow particles of Comparative Example 8, had a low weight reduction rate and an increased specific gravity increase rate. This is thought to be because the hollow particles had a small volume average particle size, so that a sufficient shell thickness could not be obtained, and the hollow particles were crushed during kneading with the thermoplastic resin or molding. From the results of Comparative Example 8, it was confirmed that even if a polar resin and a surfactant, sodium dodecylbenzenesulfonate, were used in combination, the effect obtained by combining a polar resin and a poorly water-soluble inorganic metal salt could not be obtained.

[0114] In Comparative Example 10, glass balloons, instead of hollow particles, were kneaded with a thermoplastic resin to obtain a molded body, and therefore the molded body of Comparative Example 10 had a significantly low weight reduction rate of 0% and an increased specific gravity increase rate. This is believed to be because the glass balloons could not withstand the load during kneading and broke.

[0115] On the other hand, in Examples 1 to 9, a polar resin was added to the mixed liquid, and magnesium hydroxide, a poorly water-soluble inorganic metal salt, was used as a dispersant to be added to the aqueous phase. Therefore, the obtained hollow particles had a volume average particle size within an appropriate range, a porosity within an appropriate range of 50 to 90%, and a reduced amount of residual hydrocarbon solvent. The molded bodies using the hollow particles obtained in Examples 1 to 9 all had a high weight reduction rate of 3.9 to 6.0% and a low specific gravity increase rate of 0.2 to 2.2%, and thus the crushing of the hollow particles during kneading with the thermoplastic resin and molding was suppressed. This is presumably because the thickness of the shell is controlled to an appropriate value by adding a polar resin to the mixed liquid and using magnesium hydroxide, a poorly water-soluble inorganic metal salt, as a dispersant added to the aqueous phase, thereby suppressing an increase in the amount of residual hydrocarbon solvent and increasing the mechanical strength of the hollow particles. Among them, in Examples 1 to 3, 5, and 7 to 8 in which the amount of polar resin added was 1.0 to 2.0 parts by mass per 100 parts by mass of the total mass of the polymerizable monomer, the obtained hollow particles were less likely to be crushed and the amount of residual hydrocarbon solvent was further reduced. Furthermore, SEM observation of the hollow particles obtained in Examples 1 to 9 showed that, for all of the hollow particles, 5 or less out of 100 hollow particles had continuous holes with diameters of 10 nm to 500 nm or crack-like defects with lengths of 1 μm or more. This confirmed that, in Examples 1 to 9, hollow particles having substantially no continuous holes or defects were obtained. [Explanation of symbols]

[0116] 1 Aqueous medium 2 Low polarity material 3. Dispersants 4. Monomer Composition 4a Hydrocarbon solvents 4b Materials other than hydrocarbon solvents 4c Polymerizable monomers dissolved in aqueous media 5. Oil-soluble polymerization initiator 6. Shell 8 Hollow part 10 droplets 20 Precursor particles 51 Aqueous media 53 Surfactants 54 Monomer Composition 54c Monomers dissolved in aqueous media 55 Water-soluble polymerization initiator 60 Miselle 60a Micelle precursor 100 hollow particles

Claims

1. A method for producing hollow particles having a shell containing a resin and a hollow portion surrounded by the shell, the hollow particle having a porosity of 50% or more and 90% or less, comprising the steps of: a suspending step of suspending a mixture containing a polymerizable monomer for the shell, a polar resin selected from the group consisting of polymers containing a repeating unit containing a heteroatom, a hydrocarbon solvent, a poorly water-soluble inorganic metal salt as a dispersant, and an aqueous medium to prepare a suspension in which droplets of a monomer composition containing the polymerizable monomer for the shell, the polar resin, and the hydrocarbon solvent are dispersed in the aqueous medium; A polymerization step of subjecting the suspension to a polymerization reaction; and a hydrocarbon-based solvent removal step of removing the hydrocarbon-based solvent contained in the hollow particles obtained in the polymerization step.

2. 2. The method for producing hollow particles according to claim 1, wherein the mixed solution contains 0.1 to 10 parts by mass of a polar resin based on 100 parts by mass of the shell polymerizable monomer.

3. The method for producing hollow particles according to claim 1 or 2, wherein the polar resin is an acrylic polymer.

4. 4. The method for producing hollow particles according to claim 3, wherein the acrylic polymer as the polar resin is a copolymer of polymerizable monomers for polar resins, the copolymerization ratio of the methyl methacrylate being 50.0% by mass or more and 99.9% by mass or less, and the copolymerization ratio of the polar group-containing (meth)acrylic monovinyl monomer being 0.1% by mass or more and 5.0% by mass or less, relative to 100% by mass of the total polymerizable monomers for polar resins.

5. The method for producing hollow particles according to claim 1 , wherein the poorly water-soluble inorganic metal salt serving as the dispersant is magnesium hydroxide.

6. 6. The method for producing hollow particles according to claim 1, wherein the polymerizable monomer for the shell contains a crosslinkable monomer in an amount of 70% by mass or more and 100% by mass or less and a non-crosslinkable monomer in an amount of 0% by mass or more and 30% by mass or less, based on a total mass of the polymerizable monomer for the shell, the total mass being 100% by mass.

Citation Information

Patent Citations

  • Large-particle-size hollow polymer microsphere, and preparation method thereof

    CN104910311A

  • Preparation method of hollow polymer microspheres

    CN108623734A

  • Hollow polymer fine particle and method for producing the same

    JP2002080503A

  • Hollow particle, manufacturing method and application of the same

    JP2011068774A

  • Manufacturing method of polymer particle

    JP2011074289A